Long term dietary supplementation of soybean oil and vitamin E and their effects on reproductive functions of sprague-dawley rats - Malik Khushi Muhammad, Naseem Bibi (2012)
An investigation was carried out to determine the effects of long term dietary fat and vitamin E supplementation on the reproductive functions of Sprague-Dawley rats. A total of 120 Sprague-Dawley 8-weeks old male and female rats were used in this 64-week trial inclusive of one week of adaptation period. The animals were assigned randomly into five groups of 24 animals each, comprising of 12 males and 12 females per group. The dietary treatment groups were CTRL (Base Diet + 5 % soybean oil + 1250 mg/kg Vitamin E), BDOnly (Base Diet only), BDVitE (base diet + 1250 mg/kg vitamin E Only), BDSBO (base diet + 5 % soybean oil only), and commercial pellet (COMM). Vitamin E supplements were given as natural α-tocopherol only. Of the five treatment diets, the CTRL and COMM diets were balanced diets. Six males and six female animals from each of the treatment group were randomly selected and sacrificed after 16 weeks of feeding (actual age = 24 weeks old). Of the remaining animals, 30 females were sacrificed after 32 weeks of treatment (actual age = 40 weeks old) to evaluate changes in the ovaries and uterine horn tissues. The remaining males were terminated at the end of the trial after 63 weeks of dietary intervention, when they are about 71 weeks old for sperm quality assessments and testicular histological studies. The samples were used for plasma fatty acid (FA) and vitamin E determination, sperm quality and testicular histological evaluation, as well as morphological evaluation of the ovarian and uterine horns accordingly. All protocols and procedures of this study were approved by the Animal Care and Use Committee, Ministry of Health Malaysia, Approval No. ACUC/KKM/02(3/2006). Vitamin E and n-6 PUFA supplementation when carried out in tandem resulted in significantly higher plasma n-6 PUFA enrichment, and plasma vitamin E in both male and female animals. This is very much evident in the CTRL and BDSBO groups which had higher n-6FA compared to others. However, there is probable upper limit of vitamin E accumulation, beyond which it becomes more difficult to further enrich blood plasma with vitamin E. This was clearly evident by the fact that the level of plasma alpha-tocopherol in the COMM group which had about 110 mg/kg vitamin E added to the diet, was only about half of those from CTRL, whose diet was enriched with 1250 mg/kg of vitamin E, or more than ten times the amount in the COMM diet. Supplementing vitamin E and n-6 PUFA fat together in the CTRL and COMM also created synergism which helped to preserve the testicular morphology and reduce the percentage of sperm abnormalities. In fact, the unsupplemented BDOnly group registered almost 60 % spermatozoa abnormalities at the age of 71 weeks compared to approximately 30 % for all other supplemented groups. This would contribute significantly towards ensuring male animals had a longer and more productive breeding expectancy. Similar effects were also noted for the female animals where both vitamin E and n-6 PUFA supplementation not only helped in the development of ovarian follicles, but also ensured significantly more mature follicles available both after 16 and 32 weeks of dietary intervention. It was also noted that for the females n-6 PUFA or fat supplementation is more potent as compared to vitamin E when given singly. In summary, both fats (n-6 PUFA) and vitamin E are essential in maintaining the normal reproductive functions of male and female rats. This study has conclusively shown that sustained dietary n-6 PUFA and Vitamin E supplementation can be used to improve semen quality, as well as ovarian activity and thus extend the breeding expectancy in both male and female Sprague-Dawley rats.